THE MAU MAU REBELLION and ITS INFLUENCE DEPARTIRE IN KENYA (1952-1960) - Madani, Amira (My University, 2017)
In this dissertation, I will focus on Kenya as case study of British imperialism to debate about what happened in Kenya from the 1950s until the 1960s. The British were interested in Kenya; Britain started influence in Kenya and made tensions. Kenya began to rebel and movement to gain independence, such movement was the Mau Mau rebellion. The queries are many such as why Britain was interested in East Africa, and about the tension that happened. Then, there are reflections on how Kenyan people reacted to what happened in their land like the Mau Mau rebellion. Focus on how the latter began, what was its nature, and what were its goals. In addition, there is interest in what the British response to that rebellion was and whether Kenya got the independence when it declared the revolt or not. The purpose of this study is to debate the possible answer to a research question related to whether Kenya got independence after the Mau Mau rebellion or due to the factors.
Keywords: British imperialism; Kenya; Mau Mau rebellion (1952-1960)